Gendered Varietal and Trait Preferences of consumers, traders and processors in the Common Bean Value Chain in Uganda: Implications for Breeding - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu (2024)
This study investigates the gendered varietal and trait preferences among consumers, traders, and processors within the common bean value chain in Uganda. The research aims to broaden the understanding of how gender and socioeconomic factors influence varietal preferences beyond the production stage, extending to other critical actors in the value chain. Key findings indicate that traits like fast cooking time, thick stew, good taste, and affordability are universally valued across all actor types. Additionally, the study explores the influence of traits such as disease resistance and marketability, revealing preferences that vary by gender and occupation. These findings highlight the importance of incorporating demand-led and gender-responsive preferences into breeding programs to enhance bean varietal adoption and food security outcomes. This study provides valuable insights to guide bean breeders in prioritizing traits that meet the needs of different actors in the value chain, ultimately supporting sustainable and inclusive agricultural development in Uganda.This study investigates the gendered varietal and trait preferences among consumers, traders, and processors within the common bean value chain in Uganda. The research aims to broaden the understanding of how gender and socioeconomic factors influence varietal preferences beyond the production stage, extending to other critical actors in the value chain. Key findings indicate that traits like fast cooking time, thick stew, good taste, and affordability are universally valued across all actor types. Additionally, the study explores the influence of traits such as disease resistance and marketability, revealing preferences that vary by gender and occupation. These findings highlight the importance of incorporating demand-led and gender-responsive preferences into breeding programs to enhance bean varietal adoption and food security outcomes. This study provides valuable insights to guide bean breeders in prioritizing traits that meet the needs of different actors in the value chain, ultimately supporting sustainable and inclusive agricultural development in Uganda.